Atomic metal–non-metal catalytic pair drives efficient hydrogen oxidation catalysis in fuel cells - Wang, Qilun (2023)
Rational design of efficient hydrogen oxidation reaction (HOR) electrocatalysts with maximum utilization of platinum-group metal sites is critical to hydrogen fuel cells, but remains a major challenge due to the formidable potential-dependent energy barrier for hydrogen intermediate (H*) desorption on single metal centres. Here we report atomically dispersed iridium–phosphorus (Ir–P) catalytic pairs with strong electronic coupling that integratively facilitate HOR kinetics, in which the reactive hydroxyl species adsorbed on the more oxophilic P site induces an alternative thermodynamic pathway to facilely combine with H* on the adjacent Ir atom, whereas isolated single-atom Ir catalysts are inactive. In H2–O2 fuel cells, this catalyst enables a peak power density of 1.93 W cm−2 and an anodic mass activity as high as 17.11 A mgIr−1 at 0.9 ViR-free, significantly outperforming commercial Pt/C. This work not only advances the development of anodic catalysts for fuel cells, but also provides a precise and universal active-site design principle for multi-intermediate catalysis. [Figure not available: see fulltext.].